"Femme ain't frail": (re)considering femininity, aging, and gender theory. Issue 1 (2nd January 2021) - McFarland, Jami; Taylor, Allison
Abstract: We analyze the intersection of femme, aging, and later-in-life disability by using the popular, contemporary slogan "femme ain't frail" to explore who is erased, excluded, and overlooked when fem(me)ininity is conceptualized as strong, fierce, and chosen. Building from Lisa Walker's position that dominant femme discourse marginalizes the experiences of aging femmes, we analyze the narratives of Amber Hollibaugh, Joan Nestle, Mary Frances Platt and Sharon Wachsler to explore femme experiences of later-in-life disability and aging, and to further trouble existing, popular constructions of femme identity that are predicated upon youth and able-bodiedness. We elaborate on discourses of femme and frailty, bringing them together to explore the ways femme is or, can be, frail. Insofar as femme is located in vulnerability, and vulnerability is associated with frailty, we see how femme might, indeed, be frail, and why this relationship is important to explore, not disavow. We contend that considerations of the frailty of fem(me)ininity can challenge the ageist and ableist orientation of contemporary femme politics and the broader cultural devaluation of fem(me)ininity.